PENGARUH LIKUIDITAS DAN SOLVABILITAS TERHADAP PROFITABILITAS PADA PT ASTRA AGRO LESTARI TBK PERIODE 2013-2022 - Indriyani, Melinda; Tita Amalya, Neneng (Journal of Research and Publication Innovation, 2024)
This study aims to determine the effect of Liquidity and Solvency on Profitability at PT Astra Agro Lestari Tbk for the period 2013-2022. The method used is quantitative method. The population used is the entire financial statements of PT Astra Agro Lestari Tbk, where the sample in the study is the balance sheet and income statement for the period 2013-2022. The data analysis used is descriptive statistical analysis, classical assumption test, simple linear regression test, multiple linear regression test, hypothesis testing includes t and F statistical tests, as well as correlation and determination coefficient tests. The results showed that liquidity has a negative and significant effect on profitability, this is indicated by the results of data processing the tcount value is greater than the ttable of -3.451> 2.365 with a sig. value of 0.011 smaller than 0.05. The Adjusted R Square value is 0.527 which indicates that Liquidity and Solvency contribute 52.7% to Profitability. Solvency has no significant effect on Profitability, this is evidenced by the results of data processing the tcount value is smaller than the t table -2.019 < t table 2.365 with a sig. value of 0.083 greater than 0.05. Simultaneous testing shows that Liquidity and Solvency simultaneously have a positive and Significant effect on Profitability, this is based on the results of data processing the Fhitung value is greater than Ftabel 6.017> 4.46 with a sig value. 0,030 < 0,05.